Step-by-step explanation:
Given the following systems of linear equations, 2x + y = 5, and 3y = 9 − 6x
The slope-intercept form is: y = mx + b, where m = slope, and b = y-intercept.
Subtract 2x from both sides:
2x - 2x + y = - 2x + 5
y = -2x + 5 ⇒ This is the slope-intercept form, where the slope, m = -2, and the y-intercept, b = 5.
Divide both sides by 3 to isolate y:
3y = − 6x + 3
[tex]\frac{3y}{3} = \frac{-6x + 9}{3}[/tex]
y = -2x + 3 ⇒ This is the slope-intercept form, where the slope, m = -2, and the y-intercept, b = 3.
y = -2x + 5
y = -2x + 3
These equations have the same slope, m = -2.
They have different y-intercepts.
y = -2x + 5 ⇒ The y-intercept is (0, 5), where b = 5.
y = -2x + 3 ⇒ The y-intercept is (0, 3), where b = 3.